2003
DOI: 10.1002/mus.10430
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of phrenic nerve conduction in multifocal motor neuropathy and chronic inflammatory demyelinating polyneuropathy

Abstract: The purpose of the study was to evaluate electrophysiologically phrenic nerve involvement in multifocal motor neuropathy (MMN) and chronic inflammatory demyelinating polyneuropathy (CIDP). The response latencies following phrenic nerve stimulation were increased in 11 of 14 (80%) patients in the CIDP group but in only 1 of 14 (8%) patients in the MMN group. The mean diaphragmatic compound muscle action potential (CMAP) was significantly lower in amplitude in the CIDP group compared to the MMN group and to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Recently, a prospective evaluation of phrenic nerve conduction was undertaken in CIDP patients, and a high incidence of subclinical involvement was reported. 8 With regard to the treatment of our patient, monthly IVIg administration resulted in modest and transient improvement for 2-3 weeks. She died from respiratory failure approximately 2 months after diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a prospective evaluation of phrenic nerve conduction was undertaken in CIDP patients, and a high incidence of subclinical involvement was reported. 8 With regard to the treatment of our patient, monthly IVIg administration resulted in modest and transient improvement for 2-3 weeks. She died from respiratory failure approximately 2 months after diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…With all due caution, we take this as an illustration of the potential usefulness of measuring phrenic velocities to better delineate the involvement of the phrenic nerve by peripheral neuropathies. This could open onto a frequency of phrenic abnormalities even higher than systematic studies of the phrenic have already shown (Macia et al, 2003;Sagliocco et al, 2003;Zifko et al, 1996).…”
Section: Charcot-marie-tooth Patients Datamentioning
confidence: 93%
“…Impairment of phrenic response is common during demyelinating neuropathy. For example, 85% of patients with chronic inflammatory demyelinating polyneuropathy (CIDP) present with phrenic conduction anomalies (Macia et al, 2003) at times responsible for acute or acute on chronic respiratory failure (Henderson et al, 2005). Abnormal diaphragm responses to phrenic stimulation are common during Guillain-Barré syndrome (Durand et al, 2005;Zifko et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent study, Macia et al [9] demonstrated a significant correlation between PN CMAP amplitude and Residual Forced Capacity as well as Total Lung capacity; however, PFTs were performed only in patients with altered PN, or clinical signs of respiratory failure. Furthermore, a correlation with PFT results was detected solely in the four patients (corresponding to one third of the group) with a reduction in the amplitude below the cut-off value set by the authors.…”
Section: Tablementioning
confidence: 96%
“…A recent study [9] demonstrated a positive correlation between a low amplitude of the diaphragmatic compound muscle action potential (CMAP) and altered pulmonary function tests (PFTs) in those CIDP patients who showed clinical signs of respiratory failure. Furthermore, abnormal values of conduction velocity of PN, even in the absence of respiratory dysfunction, have been reported in patients with acquired [3] or inherited neuropathies [1], suggesting that PN conduction studies may be able to disclose subclinical changes.…”
Section: Introductionmentioning
confidence: 98%